mMRI at 3.0 T as an evaluation tool of therapeutic response to neoadjuvant CRT in patients with advanced-stage rectal cancer - Attenberger, Ulrike; Meyer, Melissa; Rathmann, Nils-Andreas; Doyon, Fabian; Kienle, Peter; Hofheinz, Ralf-Dieter; Pilz, Lothar R.; Dinter, Dietmar; Schönberg, Stefan; Hausmann, Daniel (Anticancer research, 2017)
AIM: To assess whether multiparametric MRI (mMRI) can serve as a tool for evaluating response to chemoradiation therapy (CRT) in advanced-stage rectal cancer. PATIENTS AND METHODS: Twenty-one patients underwent a mMRI protocol at 3T before and after CRT. Two experienced radiologists evaluated the MRI measurements and inter-reader correlation was assessed. Changes in functional parameters in relation to regression, as well as pT stage were analyzed. The perfusion parameters plasma flow (PF) and mean transit time (MTT) were calculated offline using the established UMM Perfusion tool. RESULTS: Apparent diffusion coefficient values were significantly different among the different tumor RGs before CRT (p=0.041). Changes of dynamic contrast enhanced (DCE) MRI values did not reflect treatment response (PF: p=0.5; MTT: p=0.74). CONCLUSION: The results of our study population indicate that a high initial apparent diffusion coefficient value may be predictive of response to therapy following CRT.
Gesehen am 21.08.2018